2010
DOI: 10.1577/m09-127.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gears for Sampling Littoral‐Zone Fishes in Floodplain Lakes of the Lower White River, Arkansas

Abstract: Gear comparison studies are useful to fisheries managers because many aquatic systems require multiple gears to assess fish assemblages. Many previous studies have emphasized comparisons of catch per unit effort or basic community measures such as richness and diversity. Our objectives were to (1) compare fish assemblage richness, diversity, and evenness across sampling gears, (2) assess the similarity of fish assemblage structure as depicted by the different gears, and (3) compare fish assemblage–environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…Consequently, different net‐based (seining, gillnetting, fyke netting, use of baited fish traps, baited lift netting), hook‐and‐line based (angling, longline fishing) and visual fish‐sampling methods (snorkelling) as well as electrofishing were selected for the comparative study. These methods are listed in CEN () or had previously been applied or suggested for the use in lentic flood‐plain water bodies or lakes, but have to the best of the authors' knowledge never been systematically compared for their applicability to fish sampling in typical backwaters of large rivers (electrofishing and point abundance sampling in large rivers, Persat & Copp, ; electrofishing, fyke netting and seining in lakes, Fago, ; fyke netting and electrofishing in small ponds, Basler & Schramm, ; electrofishing, seining, multi‐mesh gillnetting, fyke netting in stagnant flood‐plain water bodies of large flood‐plain rivers, De Leeuw et al ., ; seining and electrofishing in flood‐plain lakes, Jurajda et al ., ; bottom trawls, fyke netting, multi‐mesh gillnetting, longline fishing, drift netting, day and night electrofishing in an impoundment of the River Inn, Schotzko & Gassner, ; fyke netting, gillnetting and electrofishing in flood‐plain lakes, Eggleton et al ., ; gillnetting, seining, trawling and hydroacoustics in lakes, Jurvelius et al ., ; gillnetting, electrofishing and hydroacoustics in alpine lakes, Achleitner et al ., ). Specifically, it was hypothesized that (1) low‐activity methods ( e .…”
Section: Introductionmentioning
confidence: 98%
“…Consequently, different net‐based (seining, gillnetting, fyke netting, use of baited fish traps, baited lift netting), hook‐and‐line based (angling, longline fishing) and visual fish‐sampling methods (snorkelling) as well as electrofishing were selected for the comparative study. These methods are listed in CEN () or had previously been applied or suggested for the use in lentic flood‐plain water bodies or lakes, but have to the best of the authors' knowledge never been systematically compared for their applicability to fish sampling in typical backwaters of large rivers (electrofishing and point abundance sampling in large rivers, Persat & Copp, ; electrofishing, fyke netting and seining in lakes, Fago, ; fyke netting and electrofishing in small ponds, Basler & Schramm, ; electrofishing, seining, multi‐mesh gillnetting, fyke netting in stagnant flood‐plain water bodies of large flood‐plain rivers, De Leeuw et al ., ; seining and electrofishing in flood‐plain lakes, Jurajda et al ., ; bottom trawls, fyke netting, multi‐mesh gillnetting, longline fishing, drift netting, day and night electrofishing in an impoundment of the River Inn, Schotzko & Gassner, ; fyke netting, gillnetting and electrofishing in flood‐plain lakes, Eggleton et al ., ; gillnetting, seining, trawling and hydroacoustics in lakes, Jurvelius et al ., ; gillnetting, electrofishing and hydroacoustics in alpine lakes, Achleitner et al ., ). Specifically, it was hypothesized that (1) low‐activity methods ( e .…”
Section: Introductionmentioning
confidence: 98%
“…The nature and challenges of large‐scale riverine research necessitated the use of multiple sampling methods in targeted habitats (Goodwin & Angermeier, ; Phelps et al , ), because A . rostrata is especially difficult to collect in the lower White River (Clark et al , ; Lubinski et al , ; Eggleton et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In Fago's (1998) comparison study of three gears which included mini-fyke nets, each of the sampling methods missed an average of four species per lake that another method captured. Furthermore, in a comparison with boat electrofishing and gill nets, Eggleton et al (2010) reported that mini-fyke nets captured the largest number of unique species. With little data overlap, this gear was able to describe a component of littoral fish communities that the other gears could not.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mini-fyke nets have been compared with other gears for assessing fish community structure. They tended to collect more fish and more species of fish than other gears, including electrofishing, gill nets, and seines (Clark et al 2007;Eggleton et al 2010;Cvetkovic et al 2012). Weaver et al (1993) also found that this gear resulted in better descriptions of littoral fish communities than did gill nets or seines.…”
mentioning
confidence: 96%